Pengaruh Sosial Media Marketing terhadap Minat dan Daya Beli Pelanggan - Heni Cahya Ramdani; Saptono Rahayu .; Rizal Fahmi . (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
Innovation is relentless, with the continuous introduction of new technologies, new business models, and new communication approaches.[1] One of the ways of business models is through social media. Social media is a platform not only users interacted and digitally communicated but also a marketing channel where consumers search and do transactions on products and services. The development of digital transformation i.e. social media increases the curiosity about how it influences purchasing power of consumers. The consumer means the millennials who are the well-adapter and users of this digital transformation. 115 students have been questioned via close questionnaires in order to facilitate this study and the result shows that social media has not shown any influence on the purchasing power of consumers, due to the combination of multi-channel on a purchase.